An in vitro model of hepatic steatosis and lipotoxicity – a focus on mitochondrial dysfunction and redox state - Jokinen, Mari (My University, 2023)
Non-alcoholic fatty liver disease (NAFLD) and alcohol-related fatty liver disease (ALD) have emerged as the leading causes of chronic liver disease worldwide. They cover a range of conditions from hepatic steatosis to steatohepatitis, fibrosis, and cirrhosis. The pathophysiological mechanisms underlying the onset and progression of NAFLD and ALD, however, remain poorly understood. Nicotinamide adenine dinucleotide (NAD), existing in a reduced (NADH) and oxidized (NAD+) form, is an important cofactor and electron carrier involved in several biological activities, including mitochondrial function. Previous research suggests that hepatic mitochondrial redox state (i.e., NADH/NAD+ ratio) and mitochondrial dysfunction could play a central role in NAFLD and ALD. This project aimed to develop an in vitro model of hepatic steatosis and cytotoxicity and to generate new information on the mechanisms underlying hepatic steatosis and cytotoxicity, with a focus on the role of mitochondrial redox state and mitochondrial dysfunction. The cytotoxicity of palmitate (PA) and ethanol (EtOH) was studied using the HepG2 cell line. The effects of compounds known to decrease the mitochondrial redox state, including mitochondrial uncouplers, artificial electron acceptors, malate-aspartate shuttle inhibitors, and metabolic substrates, were studied in hepatocytes treated with PA or EtOH. The effect of PA, EtOH, and redox-lowering compounds on the mitochondrial function of HepG2 cells was assessed by measuring the oxygen consumption rate (OCR). Our results demonstrated that PA and EtOH decreased the live-to-dead cell ratio and OCR in HepG2 cells, which indicates cytotoxicity and decreased mitochondrial respiration, respectively. In contrast, compounds known to decrease mitochondrial redox state conferred protective effects against PA and EtOH-mediated cytotoxicity by increasing the live-to-dead cell ratio and OCR in HepG2 cells. These results indicate that redox-lowering compounds protect hepatocytes from cytotoxicity and mitochondrial dysfunction mediated by PA and EtOH. Overall, the results suggest that the mitochondrial redox state could offer a promising new avenue for the treatment of NAFLD and ALD.
Keywords: NAFLD, ALD, mitochondria, redox, NAD+